Automation and new mechanical technologies changing the next industrial age - Dr. V. Basil Hans (International Journal of Manufacturing and Production Engineering, 2025)
The fast growth of automation and new mechanical technologies is changing the way industries work, making manufacturing and production systems more efficient, accurate, and flexible than ever before. This article looks at how sophisticated mechanical design, robotics, and intelligent automation technologies can work together and how they can improve productivity, lower costs, and make operations more sustainable. To show how mechanical engineers are influencing the next industrial era, we look at key topics including smart machinery, predictive maintenance, and collaboration between people and machines. The study underscores the pivotal role of innovation in transforming industrial processes and cultivating a new paradigm of industrial competitiveness and technical progress through the examination of present applications and future potential. Rosenberg's historical analyses of the varying sources and directions of technological change are confirmed by contemporary bibliometric data, in particular: (1) the growth of science-based technologies developed mainly in the R&D laboratories of large firms; (2) more pervasive improvements in production methods based on mechanical technology. it is made clear that mechanics plays a fundamental role in understanding the biological functions at all scales, in seeking to utilize biology and biological techniques to develop new materials and devices, and in the general area of bionanotechnology. While direct observational investigations are an essential ingredient of new discoveries and will continue to open new exciting research doors, it is the basic need for controlled experimentation and fundamentally-based modeling and computational simulations that will be truly empowered by a systematic use of the fundamentals of mechanics. While much attention has been given to the input dimension of multi-technology products, the economic and commercial domains have been rather ignored in previous literature. This work contributes to the management literature by linking the input resources with the market output for creating and appropriating value from technology cross-fertilization.
Keywords: Automation; Mechanical Innovations; Multi-objective Optimisation; New ideas in mechanics; intelligent manufacturing; robots